Clinical-epidemiological profile of severe community-acquired pneumonia in pregnant women - Reinaldo Elias-Sierra; Max Santiago Bordelois-Abdo; Tania Choo-Ubals; Ailyn Martínez-Urgellés (Revista Información Científica, 2021)
Introduction: pneumonia acquired in the community during pregnancy has not been characterized in the Hospital General Docente “Dr. Agostinho Neto”.